Estrategias Psicopedagógicas para el control de conductas agresivas en estudiantes de Bachillerato de la Unidad Educativa Fiscomisonal “San Felipe Neri”. - Erazo Haro, Bryan Adonix (2024)
The present investigative work has as objective to analize the relationship between the psychopedagogical strategies and the agressive behavior it is very important the human being psycosocial development to know how is his or her behavior with the others from his or her species and avoid some agressive conduct in such virtue this search is sustained with collected information from primary sources and with the assitance of professionals´ assistance related to the problem. The methodolody has a mixed approach a none-xperimental design and a correlational scope, it is basic because of its objective, for a place it is countryside, for the time it is transversal. The population is made of the Students of Unidad Educativa “San Felipe Neri” and the statistic sample is non-probabilistic and intentional; the techniques and instruments data collection were: a survey together with a questionairer in the Likert´s scale and the psychometric technique with the Buzz and Perry AQ test to measure aggressive behaviors. The data interpretations was carried out with the suggested techniques the every approached suggested according to the instrument applied: in the quantitative part for data processing, objectivity was used with the Excel program, supported with statisticians elaboration such as: tables and statistics pies, the analysis of each question reflected in the survey, in that way the globally results obtained according to the sample participation, which are the 2nd year high school students, it was verified that most of them know about the strategies and improvements that should have to get a peace and quiet atmosphere. In the qualitative approach to analysis the information, we used the manual with the scoring parameters of each question of the AQ Test, it showed us that we can find the presence of different aggressive manifestations in the school environment.